Wake-up stroke e apneia obstrutiva do sono: um estudo prospectivo sobre a capacidade motora e alterações do sono - Barreto, Pedro Rodrigues (2016)
Wake-up stroke (WUS) defines a cerebrovascular accident (CVA) detected when the individual awakens with symptoms of stroke. About 25% of cases of stroke are WUS. The role that sleep disorders and comorbidities play in these cases is yet to be established. The aim of this study is to evaluate clinical characteristics, changes in sleep-wake cycle and factors that influence the development and severity of symptoms in cases of stroke with and without WUS. This is a longitudinal study of observational nature. Patients with ischemic stroke (N=102), 28.4% with WUS, were evaluated at baseline and after 3 and 12 months. Patients (30-85 years old) were recruited from the stroke care unit of the General Hospital of Fortaleza from 2013 to 2015. We included those that had ischemic stroke in the last 15 days, NIHSS<15, stable clinical condition, and that were able to answer behavior questionnaires. The clinical and demographic characteristics and associated comorbidities were studied. A sleep recording was done with level III polygraph (Stardust® Phillips Respironics) to investigate sleep apnea. An apnea-hypopnea index (AHI)> 20 was considered the cutoff point to define the presence of obstructive sleep apnea (OSA). Questionnaires on functional performance (modified Rankin Scale – MRS), motor skills (modified Barthel Scale –MBS) and sleepiness (Epworth Sleepiness Scale – ESS) were applied. Excessive Daytime Sleepiness (EDS) was defined as an ESS> 10. Prospectiveley, pacients are evaluated (ESS, MRS, MBS) after 3 months and 12 months after the initial evaluation by telephone. In the sample studied (N = 102, 64% male), hypertension (73%), diabetes (29.4), heart disease (16.7%), physical inactivity (69.6%), smoking (32.4%) and alcohol consumption (17.6) were found. In the total sample, AHI (1.20 to 57.3), SpO2 (82-97%) and the desaturation index (5-94). We recorded AHI> 5 (92.9%), AHI> 15 (44.7%), AHI> 20 (35.3%) and AHI> 30 (11.8%) were variable. Cases with and without WUS did not differ regarding clinical and polygraphic characteristics. Type 2 diabetes was associated with WUS (OR = 0.37 CI: 0.15 to 0.92; p = 0.03). Individuals with OSA had higher waist-hip ratios (p = 0.01). Patients with EDS were younger (p = 0.009). The longitudinal evaluation showed no difference in the severity of symptoms in cases with and without WUS. Prospectiveley, cases with OSA evolved with worse functional performance (ERM, p = 0.02). Conclusion: Among patients with ischemic stroke, WUS manifests itself in about 1/3 of cases and it associates with type 2 diabetes. Those with stroke and OSA (AHI> 20) evolve with worse functional performance after one year.